Preliminary Results on the Influence of a Gluon Mass in Hadronic Scattering - Luna, E. G.S.; Martini, A. F.; Menon, M. J.; Mihara, A.; Natale, A. A. [UNESP] (AIP Publishing, 2004)
We present a description of the experimental data on forward pp and pp elastic scattering by means of a QCD-inspired model implemented with a dynamical gluon mass.